2022
DOI: 10.3390/ma15165504
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Thermal Stress Analysis of Cervical Resin Composite Restorations Containing Different Ratios of Zinc Oxide Nanoparticles: A 3D Finite Element Study

Abstract: Due to an increase in prevalence of cervical lesions, it is important to use appropriate restorative materials to reduce the incidence of secondary lesions. Owing to having antibacterial properties, cervical composite restorations containing different ratios of Zinc Oxide nanoparticles (ZnO NPs) have been analyzed using the Finite Element method to determine the optimal incorporation ratio from mechanical and thermal perspectives. A numerical simulation is conducted for a mandibular first premolar with a cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…However, there were other studies no negative impact was reported [ 52 , 53 ]. A finite study conducted by Yazdani et al supported that the addition of 5% ZnO particles into resin composite provides the best thermo-mechanical behavior [ 54 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, there were other studies no negative impact was reported [ 52 , 53 ]. A finite study conducted by Yazdani et al supported that the addition of 5% ZnO particles into resin composite provides the best thermo-mechanical behavior [ 54 ].…”
Section: Reviewmentioning
confidence: 99%